2009
DOI: 10.1007/s11664-009-0796-1
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Emitting Lead Salt Mid-Infrared Laser Structure on BaF2 (110) Substrate

Abstract: A lead salt mid-infrared laser sample grown by molecular-beam epitaxy (MBE) on a polished BaF 2 (110) substrate is studied. For improving the laser performance at higher operating temperature, a method of substrate transfer from a BaF 2 substrate to a copper heat sink is developed. The cleaved facet along the {100} plane, which is helpful for the formation of a Fabry-Pérot resonant cavity on the laser sample, is observed. Pulsed photoluminescence measurements are conducted on the laser sample step by step duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Compared with other novel manufacturing techniques, including molecular beam epitaxy (MBE), magnetron sputtering (MS), and electrochemical deposition (ED), vapor phase deposition (VPD) technology shows an evident cost-advantage besides of high-uniformity, good-reproducibility, and CMOS compatibility. Unfortunately, the performance of VPD-PbX infrared PC detectors has underperformed that of CBD-PbX PC detectors since the appearance of VPD technology in 2000, blocking the rapid development of VPD in manufacturing megapixel uncooled PbX infrared FPA detectors. Most recently, based on the development of room-temperature photoconductor-mechanism models and the clarification of crucial sensitization agents, , Qiu et al have reported a VPD-PbSe detector with peak detectivity D* up to 1.6 × 10 10 cm Hz 1/2 W –1 , which approaches the highest D* of 2.8 × 10 10 cm Hz 1/2 W –1 of the CBD-PbSe detector. , This result further confirms that VPD has a great potential and bright prospect in accelerating the industrialization of megapixel uncooled PbX FPA detectors. , …”
Section: Introductionmentioning
confidence: 99%
“…Compared with other novel manufacturing techniques, including molecular beam epitaxy (MBE), magnetron sputtering (MS), and electrochemical deposition (ED), vapor phase deposition (VPD) technology shows an evident cost-advantage besides of high-uniformity, good-reproducibility, and CMOS compatibility. Unfortunately, the performance of VPD-PbX infrared PC detectors has underperformed that of CBD-PbX PC detectors since the appearance of VPD technology in 2000, blocking the rapid development of VPD in manufacturing megapixel uncooled PbX infrared FPA detectors. Most recently, based on the development of room-temperature photoconductor-mechanism models and the clarification of crucial sensitization agents, , Qiu et al have reported a VPD-PbSe detector with peak detectivity D* up to 1.6 × 10 10 cm Hz 1/2 W –1 , which approaches the highest D* of 2.8 × 10 10 cm Hz 1/2 W –1 of the CBD-PbSe detector. , This result further confirms that VPD has a great potential and bright prospect in accelerating the industrialization of megapixel uncooled PbX FPA detectors. , …”
Section: Introductionmentioning
confidence: 99%